Carriage of Ser217Leu and Ala541Thr Variants of ELAC2 Gene and Risk Factors in Patients with Prostate Cancer in Burkina Faso. (17th December 2022) - Traoré, Aïda Djé Djénèba; Ky, Bienvenu Désiré; Traoré, Lassina; Zohoncon, Théodora M.; Zouré, Abdou Azaque; Yonli, Albert Théophane; Sombié, Herman Karim; Sorgho, Pegdwendé Abel; Elvira Bazié, Bapio Valery Jean Télesphore; Tovo, Sessi Frida Appoline; Kadanga, Essonan; Bakyono, Bélélé Siméon; et al.
Abstract : Background . Genetic factors are one of the significant contributors to prostate cancer (PCa) development, and hereditary prostate cancer 2 (HPC2) locus gene ELAC2 is considered a PCa susceptibility region. The HPC2/ELAC2 gene has been identified by linkage analysis in familial prostate cancer patients in the United States but has never been studied in Burkina Faso. The objective of the present study was to analyze the carriage of the C650T (Ser217Leu) and G1621A (Ala541Thr) mutations of the ELAC2 gene and the risk factors in prostate cancer patients in Burkina Faso. Methods . This case-control study included 76 participants, including 38 histologically confirmed prostate cancer cases and 38 healthy controls without prostate abnormalities. PCR combined with restriction fragment length polymorphism (RFLP) was used to characterize the genotypes of the Ser217Leu and Ala541Thr polymorphisms of the ELAC2 gene. The correlations between the different genotypes and risk factors for prostate cancer were investigated. Results . The C650T mutation was present in 44.73% of prostate cancer cases and 47.37% of controls. The G1621A mutation was present in 26.32% of prostate cancer cases and 15.79% of controls. We did not detect an association between prostate cancer risk and the Ser217Leu (p = 0.972 ) and Ala541Thr (p = 0.267 ) variants of the ELAC2 gene. Also, the two ELAC2 SNPs did not correlate with clinical stage, prostate-specific antigen (PSA) level at diagnosis, or the Gleason score on biopsies. However, we found that 100% of homozygous carriers of the T650 mutation have an A1621 mutation (p ≤ 0.001 ). Conclusion . Ser217Leu and Ala541Thr polymorphisms of ELAC2, considered alone or in combination, are not associated with prostate cancer risk.